IMPLEMENTASI PENDEKATAN CRT BERBANTUAN MEDIA MEDIA WORDWALL DALAM MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS XE SMA NEGERI 5 KUPANG - Dai Ndiha, Diandra; Djuli, Labu; Lakapu, Emanuel (Jurnal Lazuardi, 2024)
Abstract The aim of this research is to improve students' ability to write in class using a Culturally Responsive Teaching (CRT) approach with the help of Wordwall media. The CRT approach is a learning method used to appreciate and respect the diversity of students. Wherever, this approach will increase the effectiveness of writing poetry in the learning process. The method used in this research is called Classroom Action Research (PTK), which was carried out over two semesters of lectures. This research consists of four stages: preparation, action, evaluation, and reflection. The object of the research was 36 students in class X E of SMA Negeri 5 Kupang. The data collection methods used are observation and checking learning tasks. Qualitative descriptive analysis was used in collecting research data. The results of this research were obtained by applying the Culturally Responsive Teaching (CRT) approach. Keywords: Culturally Responsive Teaching (CRT), Writing poetry, and Wordwall.